Скифы в Китее - Молев, Е.А. (Археологія і давня історія України, 2018)
Статья посвящена результатам исследований скифских памятников городища и некрополя Китея. В научный оборот вводятся материалы исследований 1970—2012 гг., осуществленных С. С. Бессоновой и Е. А. Молевым и не освещенные в полной мере в свое время. The article is devoted to the results of studies of Scythian monuments of ancient settlement and necropolis of Kytaia. In the scientific revolution, the materials of the 1970—2012 research carried out by S. S. Bessonova and E. A. Molev and not illuminated in full in due time.